2012
DOI: 10.1186/1471-2369-13-132
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin administrated after cardiac surgery: effects on renal function and inflammation in a randomized controlled study

Abstract: BackgroundExperimentally, erythropoietin (EPO) has nephroprotective as well as immunomodulatory properties when administered after ischemic renal injury. We tested the hypothesis that different doses of recombinant human EPO administered to patients after cardiac surgery would minimize kidney lesions and the systemic inflammatory response, thereby decreasing acute kidney injury (AKI) incidence.MethodsIn this double-blinded randomized control study, 80 patients admitted to the ICU post-cardiac surgery were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 30 publications
2
80
0
Order By: Relevance
“…To date, preoperative administration of EPO and RIPC are two putative renoprotective interventions that have been studied in animal models and clinical trials. In early rodent (8,19,23,27), porcine (25) and clinical (26) studies, preoperative EPO administration showed promise for reducing aspects of AKI, but further clinical studies have subsequently proved disappointing (7,9). In contrast, a number of F875 RENOPROTECTION BY EPO OR RIPC clinical studies have shown that, after RIPC before surgery, acute injury to organs (either heart, liver, brain, or kidney) was significantly reduced (3,12,14,30), but negative results have also been reported (17,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, preoperative administration of EPO and RIPC are two putative renoprotective interventions that have been studied in animal models and clinical trials. In early rodent (8,19,23,27), porcine (25) and clinical (26) studies, preoperative EPO administration showed promise for reducing aspects of AKI, but further clinical studies have subsequently proved disappointing (7,9). In contrast, a number of F875 RENOPROTECTION BY EPO OR RIPC clinical studies have shown that, after RIPC before surgery, acute injury to organs (either heart, liver, brain, or kidney) was significantly reduced (3,12,14,30), but negative results have also been reported (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot clinical study reported encouraging preliminary results (26). However, substantial clinical evidence for renoprotection by EPO is lacking (7,9). In contrast, remote ischemic preconditioning (RIPC), in which short-term (1-5 min), nonlethal episodes (3-5 cycles) of limb ischemia remote to the organ of interest result in attenuated tissue injury during subsequent longer-term ischemia and reperfusion, has been reported to offer considerable protection against ischemia-reperfusion (IR)-induced organ damage.…”
mentioning
confidence: 99%
“…First, as our results indicate, the percentage of patients requiring renal replacement therapy was higher in the current trial compared with other studies [11,12]. Thus, the employment of a single preventive strategy to mitigate the development of AKI may not be enough to inhibit the numerous interconnections of signaling pathways that lead to renal injury.…”
Section: Discussionmentioning
confidence: 54%
“…One finding that supports an anti-inflammatory role for EPO is that the biologic effects of EPO and TNF-α are antagonistic, each capable of suppressing the synthesis and activity of the other [31]. In addition, several animal studies have documented that the concentrations of pro-inflammatory proteins are reduced following EPO administration, [3137] as is the expression of the genes for these proteins [5,38]. The pattern we see, then, could represent an anti-inflammatory response to the presence of pro-inflammatory cytokines, waxing and waning with the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%